2006
DOI: 10.1063/1.2172235
|View full text |Cite
|
Sign up to set email alerts
|

Use of a long-duration ns pulse for efficient emission of spectral lines from the laser ablation plume in water

Abstract: The effect of pulse duration upon the line profile of Cu I emission observed by laser ablation of a copper metal plate immersed in water has been examined. By irradiating a pulse with the duration longer than 40 ns the spectral profile with clear narrow emission lines of Cu atoms is obtained, while the emission spectra always suffer from broadening and self-absorption by the irradiation of the 20 ns pulse for the ablation. The results show that the use of a long-duration pulse enables in situ elemental analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 10 publications
2
60
0
Order By: Relevance
“…It has been demonstrated among others that pulse duration can affect the LIBS signal intensity and line shape. 30,39 More experiments would be necessary in order to confirm this possible contribution.…”
mentioning
confidence: 99%
“…It has been demonstrated among others that pulse duration can affect the LIBS signal intensity and line shape. 30,39 More experiments would be necessary in order to confirm this possible contribution.…”
mentioning
confidence: 99%
“…The next major development took place when it was demonstrated that the long-pulse laser excitation technique, which uses a single-pulse of duration $150 ns (Sakka et al, 2006(Sakka et al, , 2009, can offer significant enhancements in signal quality compared to a conventional single-pulse (with pulse durations of o20 ns) for both solids immersed in water and also bulk ionic solutions (Thornton et al, 2014a). In both cases, no significant degradation in signal quality was seen for external pressures up to 30 MPa.…”
Section: Underwater Libs At High Pressurementioning
confidence: 98%
“…While the prototype I-SEA was built using commercially available lasers and spectrometers, the components of ChemiCam are almost entirely custom made. In particular, the specifications of the long-pulse laser used in the laboratory experiments (Sakka et al, 2006(Sakka et al, , 2009Thornton et al, 2013Thornton et al, , 2014a are not met by any commercially available laser and a significant investment of effort was required to develop a robust, compact long-pulse laser that can be incorporated into a field deployable LIBS instrument. While the application of a longpulse laser is seen as the key technology for the realization of deep-sea LIBS, a number of other technical issues have also been overcome and are described in the next section.…”
Section: Underwater Libs At High Pressurementioning
confidence: 99%
“…for immersed solids [12]. Meanwhile, it has also been demonstrated that the use of a long-duration pulse N 100 ns can yield significant enhancements in signal quality for underwater samples [15,16]. It has further been shown that well resolved spectra can be observed for both bulk liquids [17] and submerged solids [18] at pressures of up to 30 MPa with little effect of external pressure using a long-pulse technique.…”
Section: Introductionmentioning
confidence: 93%